A Secure Skim Pinjaman Buku Teks with Two-Factor Authentication for SK Jempol - Norazam, Nur Farah Zahidah; Abd Warif, Nor Bakiah (Applied Information Technology And Computer Science, 2024)
A secure Skim Pinjaman Buku Teks (SPBT) with two factor authentication for SK Jempol is a web-based system that manage textbook borrowing and returning process. The major purpose for development of this system is to help SK Jempol SPBT management become secure and systematic. Two-factor authentication applied which is strong password and email One Time Password (OTP) can enhance the security of the system. OTP code will be sent to the user’s email every time they log in to the system. Throughout the system, SPBT coordinator teacher can manage SPBT prefect, student, and textbook. SPBT prefect can scan the QR code on textbook during the borrowing and returning process. QR code help the system become more efficient and systematic. The methodology used in this project is iterative waterfall. For both system interface and functionality testing result, all users were satisfied with the system’s interface, and the system functionality successfully met all the requirements. At the end of the project, a secure Skim Pinjaman Buku Teks with two factor authentication will be valuable to SPBT management throughout the whole borrowing and returning process of textbook.